Stevens' Handbook of Experimental Psychology and Cognitive Neuroscience 2018
DOI: 10.1002/9781119170174.epcn205
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Haptic Perception

Abstract: When we interact with an object, neural signals from the skin, joints, and muscles convey information about the shape, size, weight, and texture of the object. If the object is moving across the hand, information about its direction and speed is also available. In this chapter, we discuss the sensory signals the hands send the brain about our interactions with objects and review what is known about how different areas of the brain interpret these signals. Focusing on the senses of touch and proprioception, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 239 publications
0
15
0
Order By: Relevance
“…Both the increase in RMS velocity of texture-evoked vibrations and the shift to higher frequencies explains why the effect of speed is most pronounced in the responses of PC fibres, weaker in RA fibres, and weakest in slowly adapting (SA1) fibres [23]. Indeed, PC fibres are sensitive to the rate of displacement of the skin [24] and peak in sensitivity at the high frequencies (greater than 100 Hz) [25]; RA fibres are also sensitive to vibratory speed but peak in sensitivity at intermediate frequencies; SA1 fibres are least sensitive to vibratory speed and peak in sensitivity at low frequencies. While the peripheral representation of texture is highly speed dependent, afferent signals are differentiated downstream-spatially and temporally-and these neural computations give rise to a more speed-independent representation of texture [26].…”
Section: Implications For Tactile Texture Perceptionmentioning
confidence: 99%
“…Both the increase in RMS velocity of texture-evoked vibrations and the shift to higher frequencies explains why the effect of speed is most pronounced in the responses of PC fibres, weaker in RA fibres, and weakest in slowly adapting (SA1) fibres [23]. Indeed, PC fibres are sensitive to the rate of displacement of the skin [24] and peak in sensitivity at the high frequencies (greater than 100 Hz) [25]; RA fibres are also sensitive to vibratory speed but peak in sensitivity at intermediate frequencies; SA1 fibres are least sensitive to vibratory speed and peak in sensitivity at low frequencies. While the peripheral representation of texture is highly speed dependent, afferent signals are differentiated downstream-spatially and temporally-and these neural computations give rise to a more speed-independent representation of texture [26].…”
Section: Implications For Tactile Texture Perceptionmentioning
confidence: 99%
“…Quality, on the other hand, is determined by the specific spatiotemporal pattern of activation elicited in the nervous system. Some patterns of activation give rise to a texture percept, others to a vibration percept, and others to a motion percept, and these patterns co-occur and are multiplexed in the nerve 22 . Furthermore, quality is shaped in part by which classes of tactile nerve fibers are activated by the stimulus 23 .…”
Section: Stimulation Frequency Shapes Sensory Qualitymentioning
confidence: 99%
“…The modeling of impulse-response functions obtained from vector autoregressive (VAR) analysis revealed that distinct sets of pairwise exchanges of multifractal fluctuations entailed accuracy in heaviness and length judgments. These results suggest that the accuracy of perception via dynamic touch hinges on specific flowing patterns of multifractal fluctuations that people wear on their anatomical sleeves.Research into haptic perception typically concentrates on mechanoreceptors and their supporting neuronal processes, such as mechanoreceptor physiology and neuronal processing of passive somatosensory feedback [1,2]. Despite the significant insights of this research, this focus risks ignoring crucial aspects of active perception.…”
mentioning
confidence: 99%
“…Research into haptic perception typically concentrates on mechanoreceptors and their supporting neuronal processes, such as mechanoreceptor physiology and neuronal processing of passive somatosensory feedback [1,2]. Despite the significant insights of this research, this focus risks ignoring crucial aspects of active perception.…”
mentioning
confidence: 99%